EFFICACY OF INTERDISCIPLINARY INTEGRATION IN STUDY OF HUMAN ANATOMY - Попадинець, О.Г. (World of Medicine and Biology, 2014)
Interdisciplinary integration of medical disciplines in today’s conditions organizes knowledge, skills, abilities; helps to understand better the facts, phenomena and processes, promotes awareness of knowledge necessity of a particular educational course. Applying the “case”- method allows to develop the ability to use knowledge of different disciplines in unusual situations, helps to think logically when solving tasks in the students. The effectiveness of the application of Latin and English knowledge during the lessons on Human Anatomy and vice versa was analyzed.